Research on the surface oxidation procedure of Fe-base metallic glass during wet oxidation treatment - Kang, Eun Young; Chung, Young Hoon; Ok, Myoung-Ryul; Baik, Hong Koo (ELSEVIER SCIENCE SA, 2007)
Internal structure of magnetic core for high-frequency use could be divided into small insulating units to minimize eddy current loss. Accordingly, the powder size of Febal.Si9.6B14.4Nb4 (numbers indicate at.%) amorphous alloy should be small and covered with some degree of insulating layer for producing high-frequency magnetic core. In this investigation, formation of the insulating layer on the surface of Fe-based amorphous alloy powder was studied using wet oxidation method. The size of Fe-Si-B-Nb amorphous alloy powder used in this research was less than 75 mu m in diameter. Forming mechanism of surface cracks and consecutive oxide layers was explained and the thickness of insulating layer could be controlled by changing treatment time and concentration of HNO3 in the oxidizing solution. Even though the oxide layer on the powder surface was partially flaked off during hot-compacting process, sufficient electrical resistance was maintained to lessen eddy current loss effectively. (c) 2006 Published by Elsevier B.V.
Keywords: ALLOYS